2023
DOI: 10.1111/jeb.14142
|View full text |Cite
|
Sign up to set email alerts
|

Not just the sum of its parts: Geographic variation and nonadditive effects of pyrazines in the chemical defence of an aposematic moth

Abstract: Chemical defences often vary within and between populations both in quantity and quality, which is puzzling if prey survival is dependent on the strength of the defence. We investigated the within‐ and between‐population variability in chemical defence of the wood tiger moth (Arctia plantaginis). The major components of its defences, SBMP (2‐sec‐butyl‐3‐methoxypyrazine) and IBMP (2‐isobutyl‐3‐methoxypyrazine), are volatiles that deter bird attacks. We hypothesized that (1) variation in the chemical defences of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…However, we did not find any differences between the predators’ hesitation time (i.e., latency) to “attack” the bait soaked with fluids from male moths raised on high-protein and the latency to attack baits with water (control), which suggests that the predators may not perceive a difference in the odour (volatile compounds) of both. These results agree with previous studies suggesting that the defensive fluids of wood tiger moths may contain several repulsive compounds, not only pyrazines, that influence defence efficacy in concert (see also Winters et al 2021; Ottocento et al 2022) and affect predator response in different ways (Rojas et al 2019; Winters et al 2021). Moreover, as Ottocento et al show, the relative amount of the two methoxypyrazines (SBMP, IBMP) present in the wood tiger moth defensive fluids is more relevant to predator deterrence than the total amount of pyrazines.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, we did not find any differences between the predators’ hesitation time (i.e., latency) to “attack” the bait soaked with fluids from male moths raised on high-protein and the latency to attack baits with water (control), which suggests that the predators may not perceive a difference in the odour (volatile compounds) of both. These results agree with previous studies suggesting that the defensive fluids of wood tiger moths may contain several repulsive compounds, not only pyrazines, that influence defence efficacy in concert (see also Winters et al 2021; Ottocento et al 2022) and affect predator response in different ways (Rojas et al 2019; Winters et al 2021). Moreover, as Ottocento et al show, the relative amount of the two methoxypyrazines (SBMP, IBMP) present in the wood tiger moth defensive fluids is more relevant to predator deterrence than the total amount of pyrazines.…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, however, it is not possible to quantify the amount of pyrazines and conduct bird assays with the defensive fluids of the same individual. Interestingly, the same study (Ottocento et al, 2022) showed that predator responses are stronger towards the chemical defences of individuals originating from populations with high predation pressure (e.g., Scotland; Rönkä et al 2020) than towards individuals from populations with lower predation pressure, even if the total amount of pyrazines in the defensive fluids does not differ among populations. Our results show that highly melanised male moths from both diet treatments have more effective chemical defences than those with less melanin, hinting at a positive correlation between costly melanin pigments and chemical defences.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Testing theoretical predictions about the effects of multiple defences on predator cognition will require carefully designed experiments involving manipulation of prey defensive traits (Ottocento et al, in press; Rojas et al, 2019) as well as costs and benefits associated with predator decisions to attack or avoid (Sherratt & Holen, 2018). As cognition and hunting strategies of predators, and their sensitivity to prey defences can vary greatly, model predators should be as ecologically relevant as possible.…”
Section: The Functional Perspective: Predator Cognition and Multiple ...mentioning
confidence: 99%